Stress transfer mechanism and engineering practice of hydraulic fracturing roof cutting in roadway - Gu GONG; Zenghui LIU; Ruofei ZHANG; Junbao ZHANG; Ziyang WU; Fantai MA (Meikuang Anquan)
Aiming at the problem that the hard roof in the goaf is difficult to collapse, which causes severe mine pressure in the roadway, the transport roadway in the eighth mining area of Jingfang Coal Mine is taken as the engineering background, through theoretical analysis, numerical simulation and field measurement, the stress transfer mechanism of the roadway is studied by using hydraulic fracturing technology. The results show that the optimal height of pre-splitting and roof cutting from the 3-8072 coal roadway to the coal pillar side is 25 m, and the optimal angle is 30°. After roof cutting, the high stress near the transport roadway in the mining area is obviously reduced, and the vertical stress on the coal pillar side is reduced from 33.79 MPa to 17.7 MPa, with a decrease of 47.6 %; after hydraulic fracturing, the arch foot of the transport roadway in the mining area is cut off, as a result, the arch foot moves to the right and remains stable for a long time due to the large structure of the macroscopic stress shell. Through this technology, the hanging roof structure of hard roof can be changed, and the transmission of high stress to roadway can be blocked, thus the roadway is effectively protected.